Cannery Row movie still. - Chai Productions:::Creator::::::::::::
Cannery Row movie still. Doc (Nick Nolte) and Suzy DeSoto (Debra Winger) looking longingly into each other's eyes over dinner. RESTRICTED USE Digital copy only. No hard copy.